Una aproximación a la imagen cultural de España a través de sus tópicos históricos y literarios más significativos - Cano Jiménez , Gema (Historia y Comunicación Social, 2010)
This short work, which is introduced here, belongs to a bigger study where I analyse the cultural clichés about Spain from three points of view: the first, the one generated by ourselves. The second, the commonplaces generated from outside, specially from foreign literature and journalism. Finally, in the last part, I analyse if the present cultural policies try to overcome these clichés, or if on the contrary, they reproduce them, or if in a third way, these policies are building new ones such as our modernization. The following essay is a brief summary of the first aforementioned part: an approach to the cultural image of Spain through the historical and literary construction written by ourselves and foreigners.
Keywords: Cultural Image; Spain; Literary historical clichés